Determinação de parâmetros de qualidade para formas farmacêuticas homeopáticas - Cabe, Carolina Moraes (2012)
All medicine, whether allopathic or homeopathic, must go through strict quality control, which must ratify their characteristics throughout the period of validity. During the time of preparation and storage, solutions of the drugs are in permanent contact with packaging materials that can release undesirable substances to the solution. Several factors may influence the release of packing materials, and factorial design (FD) is a useful tool for analyzing the phenomenon. The aim of this study was the determination of quality parameters for Homeopathic solid (globules) and liquid (drops) dosage forms. It was carried out analysis in homeopathic globules for weight variation, mechanical strength, and moisture content uniformity. For liquid preparations, standard solutions were prepared from natural rubber bulbs, which were subjected to exhaustive extraction with two ethanol solutions (30 and 70%) in the ultrasonic bath for 20 minutes at 25°C and 50°C in three successive cycles. Studies of transfer have been made within five days, by spectrophotometric analysis in the UV region at 312 nm with λmáx and 323 nm for samples in 70% ethanol and 30% respectively. PH values were analyzed. We also conducted two FD studies, where the first, the three-level variables were solvent (chloroform, ethanol and nhexane), sample mass (30, 60 and 90mg), particle size (large disk, small disk and powder sample). In the second study, the solvent level variables were different ethanolic degrees (EtOH 30%, 70% and pure). The percentage of lending in the solutions was 5.5%, 12.4%, 24.2% and 41% of the total estimated in the reference solution. The values of rate constants of transfer were determined in the order of 0.0134 days-1 and 0.0232 days-1 in absorbance values, the solutions in ethanol at 30% and 70% respectively. These results suggest that the speed of transfer of materials from rubber is affected both by the nature of the vehicle as by the temperature